PHILOSOPHICAL QUESTIONS AND BIOLOGICAL FINDINGS, PART I: HUMAN COOPERATIVITY, COMPETITION, AND AGGRESSION: with Marcia Pally, "Philosophical Questions and Biological Findings, Part I: Human Cooperativity, Competition, and Aggression"; and Marcia Pally, "Philosophical Questions and Biological Findings, Part II: Play, Art, Ritual, and Ritual Sacrifice.". Issue 4 (26th September 2020) - Pally, Marcia
Abstract: This first part of a two‐part article illustrates how research in evolutionary biology and psychology illuminates questions arising in philosophy—specifically questions about the origins of severe, systemic aggression that arise in the mimetic theory of René Girard. Part I looks at: (i) how old the systemic practice of severe aggression is, (ii) how much results from humanity's mimetic/social and competitive nature and how much from ecological, resource, and cultural conditions, and (iii) if ecological and cultural conditions are important, might we adapt them toward greater cooperativity today? After briefly reviewing mimetic theory, the article looks at evolutionary psychology and biology, including fossil and archeological evidence. Findings suggest that severe, systemic aggression might be relatively recent and that its occurrence depends on ecological/resource/socioeconomic conditions additional to our mimetic/social nature. Thus, distinguishing the conditions that prod aggression from those that support pro‐social behavior might aid us in structuring society today.